PEMANFAATAN DANA OTONOMI KHUSUS DALAM MENDUKUNG KINERJA PEMERINTAH DI PROVINSI ACEH - Maria Ekowati (Jurnal Media Birokrasi, 2020)
Ten years has passed since a memorandum of understanding between the Government of the Republic of Indonesia and the free Aceh Movement (GAM) in Helsinki, Finland dated August 15, 2005. The memorandum of understanding is that behind the disagreement of Law No. 11 year 2006 about the government of Aceh. This research explores the implementation of special autonomy funds in the Aceh government. By using the data of the government ????inancial report of Aceh Year 2017 (Audited). The results of Research analysis showed that the utilization of special autonomy funds can improve Acehgovernment performance. Theuse of special autonomy funds as mandated in the legislation used to ????inance the 7 (seven) developments in the province of Aceh, namely infrastructure, economics, poverty, education, social and health, including the implementation of Aceh privileges. With the proper ????inancing of development for the entire sector is expected to be a strong thrust for the province of Aceh in spur development. Keywords: dana special autonomy; performance; economic growth; and the Aceh government